Intestinal parasitic contamination in commonly consumed vegetables from wet markets in Pulau Pinang: a pilot study / Balkis Ballina Ukhra Yunus, Zeti Norfidiyati Salmuna and Azlinda Abu Bakar - Ukhra Yunus, Balkis Ballina; Salmuna, Zeti Norfidiyati; Abu Bakar, Azlinda (Faculty of Applied Sciences, 2023)
Eating raw vegetables is one of the parasites' modes of transmission to humans. This study aimed to screen and investigate the occurrence of parasitic intestinal contamination in commonly consumed vegetables among Malaysian from local wet markets in Pulau Pinang. In this study, the vegetables selected were Brassica oleracea (cabbage), Centella asiatica ('pegaga'), Daucus carota (carrot), Ipomea aquatica (water spinach or 'kangkung'), and Oenanthe javanica ('selom'). One kilogram of each vegetable was purchased randomly from two wet markets in the Northeast and Southeast districts of Pulau Pinang, respectively. Specimens were processed using the sedimentation technique and standard wet mount microscopy. The specimens were examined for the presence of ova (parasite's egg) or larvae under an Olympus optical microscope. The results revealed that vegetables from both wet markets were contaminated with soil-transmitted helminths (STH) and other intestinal parasites, with pegaga being the most contaminated vegetable. Out of the 200 slides examined, these vegetables were contaminated with at least one type of parasite: 'pegaga' 35 % (n=14), selom 17.5 % (n=7), cabbage 10 % (n=4), carrot 5 % (n=2) and water spinach or 'kangkung' 2.5 % (n=1). Of these, the parasites that were found in the specimens were Ascaris sp. (70.59 %), followed by hookworm (17.65 %), Fasciolopsis sp. (8.82 %), and Strongyloides sp. (2.94%). This study highlighted the importance of raising awareness among the community to prevent STH infections. This can be done by promoting good hand hygiene practices and educating on how to prepare uncooked vegetables properly.